An electrochemical study of the nickel hydroxide-gold modified electrode employing the surface resistance technique - Tucceri, Ricardo (2016)
Simultaneous cyclic voltammetry (CV) and surface resistance (SR) measurements were employed to study the electrochemical behaviour of the nickel hydroxide-gold modified electrode. To this end, firstly, gold film electrodes of different thicknesses were synthesized, and their CV and SR responses within the potential regions corresponding to hydroxide ion adsorption (OHads) and gold oxide (AuO) formation in alkaline medium were analysed. Then, these gold film electrodes were modified with different nickel hydroxide surface coverages, and their CV and SR responses were compared with those of bare gold films within the same potential regions and electrolyte solution. While cyclic voltammetric responses of the bare gold film electrode and the nickel hydroxide-gold film modified electrode are practically the same within the whole potential range − 0.5 V < E < 0.35 V (SCE), SR responses are the same only within the potential range − 0.3 V < E < 0.35 V. Strong differences between the SR responses of the bare gold electrode and the nickel hydroxide-gold modified electrode within the potential range comprised between − 0.5 V and − 0.3 V are observed. SR data were interpreted in terms of the field effect and size effect theories formulated to study adsorption processes at thin metallic films. With regard to the bare gold film electrode, the field effect theory allows one to conclude that within the potential region corresponding to hydroxide ion adsorption, 77% of the electron density charge of gold is involved in the hydroxide ion–gold interaction. Besides, a linear relation between the surface resistance change (ΔR) and the degree of oxidation (θox) at fixed gold film thickness (ϕm) is obtained within the potential region corresponding to gold oxide formation. In agreement with the size effect theory, the ΔR/θox slope exhibits a linear dependence on ϕm− 2. The same SR responses for the nickel hydroxide-gold modified electrode and the bare gold electrode within the potential range − 0.3 V < E < 0.35 V indicate that the nickel hydroxide layer does not directly interact with the gold film surface. However, after the reduction of OHads and AuO layers, at potential values more negative than − 0.3 V (SCE), an increase of the surface resistance is observed for the nickel hydroxide-gold modified electrode, which was attributed to nickel adatoms that directly interact with the gold film surface. On the basis of the electron conduction scattering model employed to describe the interaction of a metal film surface with a foreign atom layer, one can conclude that nickel film growth involves an initial stage in which nickel islands and then, compact structures are formed.